Gambaran Masalah Keperawatan pada Anak dengan Kejang Demam di Rumah Sakit Perkebunan Wilayah Karesidenan Besuki - Oktalia Rahmawati Rahayu; Lantin Sulistyorini; Dini Kurniawati (Pustaka Kesehatan, 2021)
A febrile convulsion is a neurological health problem in children age six months to 5 years. The increased temperature will cause horrible impacts to children, such as severe hypoxia, increased capillary permeability, brain edema, which can damage the neuron. The main problem of nursing in febrile convulsion is hyperthermia management. This research is retrospective descriptive and sampling technique total sampling on 161 participants. The data were obtained from the medical record in the estate hospital in the area of Besuki residency. The result shows that the most frequent nursing problem from febrile convulsion children is Hyperthermia 93,8%. The febrile convulsion that triggers hyperthermia is caused by an increased metabolism rate of 23,0% and has a nursing problem of 96,9%. Nursing problems that arise due to febrile convulsion consequence most often hyperthermia. Furthermore, other nursing problems that arise in child febrile convulsion are the ineffectiveness of airway clearance and ineffective breathing patterns. Other problems also arise, such as lack of fluid volume, ineffective tissue perfusion, ineffective brain perfusion, risk of falls, and injury.